One‐Pot Double Benzylation of 2‐Substituted Pyridines using Palladium‐Catalyzed Decarboxylative Coupling of sp2 and sp3 Carbons. Issue 16 (19th October 2014) - Wang, Yaping; Li, Xinjian; Leng, Faqiang; Zhu, Helong; Li, Jingya; Zou, Dapeng; Wu, Yangjie; Wu, Yusheng
Abstract An efficient and practical decarboxylative double benzylation method for various 2‐picolinic acids has been established by using a bimetallic catalytic system of palladium(II) chloride (PdCl2) and silver(I) oxide (Ag2O), which offered a variety of diarylmethane derivatives with moderate to good yields. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>